Biomimetic strategies for replicating the neural stem cell niche. (February 2017) - Willerth, Stephanie M
Graphical abstract: Highlights: Neural stem cell niches provide guidance for designing stem cell microenvironment. Affinity-based delivery systems mimic the properties of the neural stem cell niche. Multivalent growth factors replicate effects found in the neural stem cell niche. Abstract : Stem cells have garnered a significant amount of attention due to their ability to become different types of mature cells, including those found in the nervous system. However, achieving uniform and reproducible differentiation of stem cells into functional neural tissue remains challenging. This review focuses on novel strategies for engineering scaffolds to replicate the cues found in the neural stem cell niche — the microenvironment present in nature that guides immature neural stem cells to become mature cells of the nervous system. This opinion piece reviews recent advances in affinity based drug delivery systems and multivalent ligands as unique methods for replicating the features found in nature that promote neural differentiation.